Ammonia and Methane Emission Factors from Cattle Operations Expressed as Losses of Dietary Nutrients or Energy - Liu, Zifei; Liu, Yang; Murphy, James P.; Maghirang, Ronaldo (My University, 2017)
The objective of this study was to conduct a systematic review of published literature on ammonia (NH3) and enteric methane (CH4) emissions from beef and dairy cattle operations to obtain statistically representative emission factors based on dietary intakes of nutrients or energy, and to identify major causes of emission variations. NH3emissions from lagoon or other manure storage facilities were not included in this review. The NH3 and CH4 emission rates, expressed as a percentage losses of dietary nutrients or energy, demonstrated much less variation compared with emission rates expressed in g/animal/day. Air temperature and dietary crude protein (CP) content were identified as two major factors that can affect NH3 emission rates in addition to farm type. Feed digestibility and energy intake were identified as two major factors that can affect CH4 emission rates expressed as a percentage losses of dietary energy. Generally, increasing productivity and feed efficiency represented the greatest opportunity for mitigating NH3 or CH4 emissions per unit of livestock product. Expressing CH4loss on a digestible energy basis rather than a gross energy intake basis can better represent the large variation among diets and the effects of varying dietary emission mitigation strategies.
Citation: Liu, Z.; Liu, Y.; Murphy, J.P.; Maghirang, R. Ammonia and Methane Emission Factors from Cattle Operations Expressed as Losses of Dietary Nutrients or Energy. Agriculture 2017, 7, 16.
Keywords: Crude Protein Content; Feeding Efficiency; Nitrogen; Forage-to-Concentrate Ratio; Digestibility; Digestible Energy